Nuclear matrix attachment occurs in several regions of the IgH locus. - Cockerill, P N (1990)
The genome is thought to be divided into domains by DNA elements which mediate anchorage of chromosomal DNA to the nuclear matrix or chromosome scaffold. The positions of nuclear matrix anchorage regions (MARs) have been mapped within the 200 kb mouse immunoglobulin heavy chain constant region locus, thereby allowing an estimate of the size of DNA domains within a segment of the genome. MARs were identified in four regions, which appear to divide the locus into looped DNA domains of 30, 20, 30 and greater than 70 kb in length. These DNA domain sizes fall within the range of DNA loop sizes observed in histone-extracted nuclei and chromosomes. In two regions, large clusters of MARs were identified, and many of these MARs lie on DNA fragments that include repetitive DNA elements, perhaps indicating that repetitive DNA integrates into the genome close to MARs, or that some classes of repeats could themselves act as MARs.